2017
DOI: 10.5944/ried.20.2.17602
|View full text |Cite
|
Sign up to set email alerts
|

Realidad Aumentada y Navegación Peatonal Móvil con contenidos Patrimoniales: Percepción del aprendizaje

Abstract: ResumenMediante la creación de una aplicación móvil de aprendizaje sobre elementos del patrimonio, relacionada con la implementación de recursos como son la Realidad Aumentada (RA) y la Navegación Peatonal Móvil (NPM), se han desarrollado procesos de formación en contextos de movilidad, enlazados con la información territorial sobre el patrimonio histórico y cultural correspondientes a las ciudades de Salamanca (España) y Santiago (Chile). El desarrollo del software se enfoca en dos grandes ámbitos: el primero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
(15 reference statements)
1
5
0
4
Order By: Relevance
“…Referring to negative attitudes, the finding found that this coincides with the diversity of research (Cabero, García, & Arroyo, 2016;Fonseca et al, 2016;Han et al, 2015;Y. Hsu et al, 2017;Joo et al, 2017;Pérez-López, 2015;Rodríguez, Naranjo, & Duque, 2016), who have clearly indicated that the students' attitudes towards the obstacles and their degree of acceptance are very significant.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Referring to negative attitudes, the finding found that this coincides with the diversity of research (Cabero, García, & Arroyo, 2016;Fonseca et al, 2016;Han et al, 2015;Y. Hsu et al, 2017;Joo et al, 2017;Pérez-López, 2015;Rodríguez, Naranjo, & Duque, 2016), who have clearly indicated that the students' attitudes towards the obstacles and their degree of acceptance are very significant.…”
Section: Discussionsupporting
confidence: 81%
“…Possibilities that when applied to teaching, show students to have high levels of satisfaction and positive attitudes for their use (Akçayır & Akçayır, 2017;Y. Hsu, Lin, & Yang, 2017;Joo, Martínez, & García-Bermejo, 2017), are motivated towards these educational actions (Cheng, 2017;Garay, Tejada, & Maiz, 2017) and improves academic performance (Lu & Liu, 2015;Tekedere & Göker, 2016;Yilmaz & Goktas, 2017).…”
Section: Augmented Reality Applied To University Educationmentioning
confidence: 99%
“…With regard to the significant way of joining the educational field, the study in this regard indicates few aspects, although the research conducted is limited but increasing [31], with this possibly being one of the great problems it has for its addition to teaching. For example, it has been shown that the students have a favorable attitude towards it, and its use increases the motivation towards learning [32][33][34], favors the creation of a constructivist context of training [31], promotes an active learning environment [7,35], which reduces the cognitive load the students are subjected to in training tasks [7,36], the students show a high degree of acceptance and positive attitudes towards the technology [37][38][39][40] and it awakens a high degree of satisfaction in the students and the teachers [39][40][41][42][43]. Also, it improves the spatial ability and orientation of the students [44,45], and its use improves academic performance [46].…”
Section: Introductionmentioning
confidence: 99%
“…De este modo no se requiere ninguna explicación magistral por parte del docente, ni la memorización de conceptos por parte del alumnado, sino que lo que interesa es proporcionar la mencionada inmediatez, garantizar la rápida asimilación de conceptos, el incremento de la motivación del alumno y el acercamiento del concepto teórico al elemento arquitectónico o constructivo real, en lugar de como habitualmente se ha venido realizando, acercando el elemento constructivo en imagen al aula. [15] En resumen, las técnicas de realidad aumentada compaginan los dos campos que se han de tratar en las enseñanzas de la construcción arquitectónica: la asimilación de los conocimientos a través de modelos ficticios que responden a una realidad. Hasta la actualidad esta tarea venía realizándose de manera interrumpida, puesto que era complicado solapar los dos ámbitos mientras que una vez que se ha generado y desarrollado una aplicación o herramienta de RA cualquier persona puede acceder a ambos campos de conocimiento simplemente con un Smartphone.…”
Section: Advances In Building Educationunclassified